1989
DOI: 10.1055/s-2007-1020310
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Different Temporary Myocardial Pacing Leads

Abstract: Temporary myocardial pacing leads are routinely used for diagnosis and treatment of postoperative arrhythmias following open-heart surgery. The intention of this study is to compare five different electrodes for reliability during the postoperative period. A standardised technique of implantation was used to place 147 ventricular and 81 atrial wire electrodes in 149 patients. During operation and then daily over the next ten days, the stimulation threshold, P- and R-wave sensing, and impedance were measured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Temporary epicardial pacing wires are routinely used for treatment and diagnosis of arrhythmias following open heart surgery procedures. Postoperative external cardiac pacing may be necessary in a number of patients for several days and therefore needs reliable temporary pacing wires 1–3,4 . These wires may not only be required for antibradycardia therapy, but also for diagnosis of supraventricular tachycardias as atrial fibrillation or may even be mandatory for overdrive pacing of atrial flutter.…”
Section: Introductionmentioning
confidence: 99%
“…Temporary epicardial pacing wires are routinely used for treatment and diagnosis of arrhythmias following open heart surgery procedures. Postoperative external cardiac pacing may be necessary in a number of patients for several days and therefore needs reliable temporary pacing wires 1–3,4 . These wires may not only be required for antibradycardia therapy, but also for diagnosis of supraventricular tachycardias as atrial fibrillation or may even be mandatory for overdrive pacing of atrial flutter.…”
Section: Introductionmentioning
confidence: 99%
“…There are two adult clinical trials that have compared bipolar temporary epicardial pacing leads with unipolar leads . These studies have been conducted on postoperative patients with coronary artery disease and have reported that bipolar temporary pacing leads maintain improved pacing in the ventricle and have better sensing capabilities in the ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…was also similar to what we found in our study. The other study in adult noncongenital patients by Wirtz et al . compared bipolar pacing leads (Osypka TME 64a/66a, Osypka TME 64/66, Osypka Medical GmbH, Berlin, Germany) to unipolar leads (Ethicon HD 12S, Osypka TME 60/60a, Medtronic 6400/6500) in 149 patients for 10 PODs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As bipolar electrodes require less energy for capture, they have a longer longevity when compared to a unipolar system. [1213] Temporary epicardial pacing leads have been used for periods of up to 3 months when patient size or other factors may preclude implantation of a permanent pacing system. [5] Steroid eluting endovascular pacing wires are available for use with permanent pacemakers and significantly reduce the inflammation around the myocardium where the wire is attached.…”
Section: Pacing Wiresmentioning
confidence: 99%